Mechanization supports women farmers’ productivity, but impact on empowerment is inclusive - Masset, Edoardo; Malhotra, Suchi Kapoor (CGIAR GENDER Impact Platform, 2024)
Mechanization is regarded as a key tool in the empowerment of women in agriculture. Mechanization is often associated with an increase in farmers’ income and time available to invest in alternative economic activities. Evidence suggests a limited but positive impact of mechanization on women’s agricultural productivity. Evidence on the specific benefits of mechanization for women and its different impacts on women and men farmers remains inadequate.